Respuesta :

Answer:

The value of 5·K(-3) - 7·K(-4) is -11

Step-by-step explanation:

The graph of the function y = K(x) is given;

Given that the graph of the function is defined in the given interval of the graph from -5 < x < 5, the value of the function is given from directly reading from the graph

The value of y at x = -3 is read from the graph as y = K(-3) = 2

The value of y at x = -4 is read from the graph as y = K(-4) = 3

Therefore;

5·K(-3) - 7·K(-4) = 5 × 2 - 7 × 3 = -11

The value of 5·K(-3) - 7·K(-4) = -11